Acute Myelomonocytic Leukemia (M4) with t (6; 9) (p23; q34) Followed by Detection of Minimal Residual Disease Using DEK-CAN mRNA - BESSHO, Fumio; YANAGISAWA, Masayoshi; TABUCHI, Ken; FENG, Xu; TATSUMI, Ken; HAYASHI, Yasuhide; OHNISHI, Hiroaki; KOBAYASHI, Miyuki (The Japanese Journal of Pediatric Hematology, 1998)
We report on a six-year-old boy who was admitted to our hospital because of high fever and exanthema. He was found to have acute myelomonocytic leukemia (AMMoL) (FAB-M4) without bone marrow basophilia. A cytogenetic analysis of bone marrow blasts revealed t (6; 9) (p23; q34). He was treated with induction therapy consisting of cytarabine, mitoxantrone and etoposide, and attained complete remission. After 8 courses of intensification therapy, chemotherapy was completed. However, 2 months later he relapsed, and the disease became resistant to chemotherapy. He died of sepsis 20 months after the diagnosis. DEK-CAN chimeric mRNA was detected both at the time of diagnosis and during hematologic remission by reverse transcriptase-polymerase chain reaction. The poor clinical outcome of our case was compatible to with previous reports of leukemia with t (6; 9). More intensive treatment, including bone marrow transplantation in the first remission, should be considered to improve the prognosis of this type of leukemia. The etiology and clinical features of t (6; 9) acute leukemia are also discussed.